Alternative splicing promotes tumour aggressiveness and drug resistance in African American prostate cancer - Bi-Dar Wang (Nature Portfolio, 2017)
In prostate cancer tumour aggressiveness can be related to race. Here, the authors identify an alternative RNA splice variant of PIK3CD as a potential mechanism to explain racial disparities in the incidence and aggressiveness of prostate cancer between African American and European American men.